TEACHING READING BY USING GIST STRATEGY VIEWED FROM THE STUDENTS’ COGNITIVE ASPECT ON THE EXTENSIVE LEVEL OF ENGLISH DEPARTMENT STUDENTS IKIP PGRI MADIUN - Nuri Ati Ningsih; Arri Kurniawan (Universitas PGRI Madiun, 2014)
This research aimed at (1) describing the implementation of GIST strategy in the process of teaching reading viewed from the cognitive aspect having by the students; (2) finding the positive aspects of the implementation of GIST strategy; (3) knowing the weaknesses of the implementation of GIST strategy in the process of teaching reading viewed from the cognitive aspect. The method in this research was descriptive qualitative. In doing the research, there were some steps to be implemented to collect the data. They were observation, interview, and documentation. Then, analyzing data was done by reducing the data, presenting the data and drawing conclusion or verification. The result of the research showed that (1) GIST has been implemented maximally by the lecture based on the characteristics of this teaching strategy. To dig up the students’ cognitive aspects, the lecture provide the specific worksheet which represents the students’ cognitive level for higher order thinking skill, (2) GIST creates the students’ character in a good manner, such as; active, responsible and confidence. They also learn how to work in a team; (3) Some weaknesses found in this research are; It needs a long time to create the instrument to support the implementation of GIST and Evaluation must be done by combining both cognitive level and the level of reading ability.